Causality between research output in the field of biotechnology and economic growth in Turkey - YAŞGÜL, YAŞAR SERHAT (SPRINGER, 2016)
Biotechnology has become one of the crucial priorities in terms of the economic growth, especially in the developing countries. As the biotechnology is a relatively new set of technologies, the potential of the countries that act early to catch up with the developments increase. The priority for this potential to emerge is research activities. Research activities lead both the growth of scientific knowledge stock and improvement of the quality of human capital. Within this context, production of scientific publication has great importance regarding research activities aimed at relatively new technologies like biotechnology. However, an empirical study that analyzes the relationship between the production of scientific publication (research output) in the biotechnology field, and economic growth was not encountered in the literature. Moreover, this study is aimed to complete this deficiency that is seen in the literature. Accordingly, from the case of Turkey, the relationship between research output in the field of biotechnology and economic growth was analyzed via bootstrapped Granger causality test. In the light of the obtained findings, it was concluded that research output in the field of biotechnology granger causes economic growth in Turkey for the period of 1981-2013. The determination of such causality relationship reveals that the scarce resources reserved for science and technology are directed to a relatively correct field of technology for a developing country that is quite new in the field of biotechnology, such as Turkey.
Keywords: Biotechnology; Turkey; Research output; Economic growth; Bootstrapped Granger causality test; INNOVATION; COINTEGRATION; SCIENCE; GDP